High improvement of degradation behavior of ZnO varistors under high current surges by appropriate Sb2O3 doping. Issue 1 (January 2021) - Wang, Manyu; Ren, Xin; Zhou, Qibin; Li, Zhuyun; Yang, Hongxiang; Jiang, Haibo; Yan, Ying; Ruan, Xuejun; Yu, Wenqi; Jin, Lujiang; Yao, Zheng; Shi, Liyi
Abstract: The effects of Sb2 O3 content on the microstructures and electrical properties of the ZnO varistors, especially on the degradation behavior under pulse current stress were studied. The results showed that the degradation behavior was effectively improved by doping appropriate amount of Sb2 O3, which attributed to the homogenized microstructure and the compression of the interstitial void. The change rates of positive and negative breakdown voltage gradients of samples doped with 0.92 mol% Sb2 O3 under 20 * 20 kA + 2 * 30 kA surges were -1.76 % and 1.56 % respectively, which was one of the best levels reported in the previous literatures. In addition, the sample exhibited excellent comprehensive electrical properties, with breakdown voltage gradient of 207.74 V mm −1, nonlinear coefficient of 119.1, leakage current density of 1.03 × 10 -2 μA cm -2, and clamping voltage ratio of 2.17 under 20 kA surge, making it a promising candidate for surge protector devices.